Semi‐distributed resource allocation and power quantization control algorithm for device‐to‐device network - Alam, Naved; Mehfuz, Shabana (International journal of communication systems, 2021)
Summary The cellular mobile communication network has been widely deployed in large regions to provide connectivity between billions of people. The population of cellular mobile users has been growing since the past decade. Therefore, we need a high capacity cellular system with extraordinary performance to meet the demand of the cellular users. To minimize the traffic load from the evolved Node Base (eNB) station, device‐to‐device (D2D) network must be deployed along with the commercial cellular network. D2D provides the direct connectivity between the proximal users without associating with eNB. This reduces the traffic load from the eNB. In other words, it enhances the capacity of the system. But D2D communication suffers a severe interference by the cellular user. In this paper, we have proposed a solution for the cross‐tier interference faced by the D2D users and eNB under uplink reuse transmission. We have proposed a semi‐distributed resource allocation and power quantization control (SRA–PQC) scheme. The simulation result shows that a better sum rate can be achieved using the proposed scheme. To minimize the traffic load from the evolved Node Base (eNM) station, device‐to‐device (D2D) network must be deployed along with the commercial cellular network. In this paper, we have proposed a solution for the cross‐tier interference faced by the D2D users and eNB under uplink reuse transmission. A semi‐distributed resource allocation and power quantization control (SRA–PQC) scheme has been proposed in the paper.